The Application of X-ray Parameters for Calculation of Mean Glandular Dose from Mammography Examination - Sookpeng, Supawitoo (Asian Health, Science and Technology Reports, 2007)
The primary purpose of this research was to develop a series of equations derived from x-ray parameters to calculate the mean glandular dose (MGD) for patients who underwent mammography in real time. A mammography x-ray generator at Buddhachinaraj Hospital in Phitsanulok, Thailand, was employed in this study. The half value layer (HVL) and exposure dose were measured by a 6-cc, ionization chamber (10x5-6M, Radcal Corporation) according to the American College of Radiology (ACR) recommendations. The measured HVL was found significantly correlated with the tube voltage. The equations for calculation of radiation exposure dose were derived from tube voltage, tube current and compressed breast thickness for both rhodium and molybdenum filters. Further, the correction factor derived from the tube voltage was used to convert exposure dose to the MGD. Thus, the MGD can be determined in real time from the tube voltage, tube current and compressed breast thickness of the patient.